2009
DOI: 10.1227/01.neu.0000334046.41985.bb
|View full text |Cite
|
Sign up to set email alerts
|

Staged Angioplasty for Carotid Artery Stenosis to Prevent Postoperative Hyperperfusion

Abstract: SAP decreased the HP phenomenon on single-photon emission computed tomography after performing these procedures in selected patients. Although additional intervention is needed, SAP is considered a relatively simple and effective method to avoid HP in patients at high risk of HP after carotid revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 23 publications
1
66
0
Order By: Relevance
“…6) SPECT was performed immediately following stenting, and no hyperperfusion was revealed. However, blood pressure was strictly controlled both during and after the procedure.…”
Section: Case Reportmentioning
confidence: 99%
“…6) SPECT was performed immediately following stenting, and no hyperperfusion was revealed. However, blood pressure was strictly controlled both during and after the procedure.…”
Section: Case Reportmentioning
confidence: 99%
“…However, they may have been too large to prevent hyperperfusion. Yoshimura et al 8,10) targeted a vascular lumen diameter of ≥2 mm using PTA balloons measuring 2.5 to 3 mm in diameter. In the future, initial treatment with a balloon measuring 3 mm in diameter should be considered when encountering similar patients.…”
Section: Casementioning
confidence: 99%
“…On the other hand, one-stage stenting should be performed when sufficient vasodilation is not achieved by PTA alone or when restenosis/reocclusion, a residual thrombus, or vascular dissociation is present. 8,10) In Case 1, a red thrombus measuring 2 cm was retrieved through a stent retriever at the site of cervical ICA occlusion. Before collection, DSA with a microcatheter at the distal occlusion site showed translucency, suggesting a thrombus at the occlusion site; the possibility of embolic occlusion could not be ruled out, and a stent retriever was initially used.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Yoshimura et al 9) reported that the use of staged angioplasty (SAP), which consisted of undersized-balloon angioplasty followed by delayed CAS, was an especially promising method for preventing CHS. 9) However, the penetration rate and efficacy of SAP in patients having a high risk of CHS in real clinical settings have yet to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%